(untitled) (Journal of Information Technologies in Education (ITE), 2008)
In this article, the authors analyze and represent the results of conducting the distance course “Practice of tutors”. The main aspects and problems of conducting distance learning are considered. So, the distance course “Practice of tutor” was conducted on the base of system of distance learning “Kherson Virtual University” of Kherson State University (www.dls.kherson.ua/dls). The main aim of this course is to teach students or teachers to create author’s distance courses and manage educational process.